2015
DOI: 10.2147/amep.s88580
|View full text |Cite
|
Sign up to set email alerts
|

Stress and burnout in residents: impact of mindfulness-based resilience training

Abstract: Background and objectiveStress and burnout impact resident physicians. This prospective study tests the hypothesis that a mindfulness-based resilience intervention would decrease stress and burnout in residents.MethodsResident physicians from the Departments of Family Medicine, Psychiatry, and Anesthesia at Duke University, Durham, NC, USA, participated in two or three 1-hour sessions of mindfulness-based resilience activities, which introduced mindful-awareness and included practical exercises for nurturing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
98
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 27 publications
5
98
0
Order By: Relevance
“…This partly concurs with previous research that found no gender differences in burnout 2. Goldhagen et al6 found that PGY1 and PGY2 females had a higher depression‐anxiety‐fatigue score than males, and mindfulness‐based intervention helped improve the scores. They speculated that women have additional demands outside of work and family planning stresses 6.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This partly concurs with previous research that found no gender differences in burnout 2. Goldhagen et al6 found that PGY1 and PGY2 females had a higher depression‐anxiety‐fatigue score than males, and mindfulness‐based intervention helped improve the scores. They speculated that women have additional demands outside of work and family planning stresses 6.…”
Section: Discussionsupporting
confidence: 91%
“…Goldhagen et al6 found that PGY1 and PGY2 females had a higher depression‐anxiety‐fatigue score than males, and mindfulness‐based intervention helped improve the scores. They speculated that women have additional demands outside of work and family planning stresses 6. Interestingly, women in our study reported significantly higher sleepiness than men, supporting the hypothesis that women may have more non‐work‐related duties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accreditation Council for Graduate Medical Education standards also state that in order for a residency program to be accredited, the program must include an awareness program to identify fatigue and sleep deprivation, and provide decent sleeping facilities, proper naps and back up plans for patient care in case a resident cannot carry out assigned duty 24. While reviewing previous related studies, we have found similar results demonstrated the existence of a significant association between female gender and sleepiness, depression scores and depressive symptoms 12,14,22,25,26. Burnout, also, was evident in young females 12.…”
Section: Discussionsupporting
confidence: 85%
“…Residency training can be quite intense and stressful for many residents. [13] This study did not look into that aspect.…”
Section: Discussionmentioning
confidence: 98%